A detailed life history of a pleistocene steppe bison (Bison priscus) skeleton unearthed in Arctic Alaska. (1st December 2020) - Funck, Juliette; Heintzman, Peter D.; Murray, Gemma G.R.; Shapiro, Beth; McKinney, Holly; Huchet, Jean-Bernard; Bigelow, Nancy; Druckenmiller, Patrick; Wooller, Matthew J.
Abstract: Detailed paleoecological evidence from Arctic Alaska's past megafauna can help reconstruct paleoenvironmental conditions and can illustrate ecological adaptation to varying environments. We examined a rare, largely articulated and almost complete skeleton of a steppe bison ( Bison priscus ) recently unearthed in Northern Alaska. We used a multi-proxy paleoecological approach to reconstruct the past ecology of an individual representing a key ancient taxon. Radiocarbon dating of horn keratin revealed that the specimen has a finite radiocarbon age ∼46, 000 ± 1000 cal yr BP, very close to the limit of radiocarbon dating. We also employed Bayesian age modeling of the mitochondrial genome, which estimated an age of ∼33, 000–87, 000 cal yr BP. Our taphonomic investigations show that the bison was scavenged post-mortem and infested by blowflies before burial. Stable carbon and oxygen isotope (δ 13 C and δ 15 N) analyses of sequentially sampled horn keratin reveal a seasonal cycle; furthermore, high δ 15 N values during its first few years of life are consistent with patterns observed in modern bison that undertook dispersal. We compared sequential analyses of tooth enamel for strontium isotope ratios ( 87 Sr/ 86 Sr) to a spatial model of 87 Sr/ 86 Sr values providing evidence for dispersal across the landscape. Synthesis of the paleoecological findings indicates the specimen lived during interstadial conditions. Our multi-proxy, paleoecological approach, combining light and heavy isotope ratios along with genetic information, adds to the broader understanding of ancient bison ecology during the Late Pleistocene, indicating that ancient bison adopted different degrees of paleo-mobility according to the prevailing paleoecological conditions and climate. Highlights: We provide paleoecological data from a rare and almost complete skeleton of a steppe bison ( Bison priscus ) from Northern Alaska. Isotope and ancient DNA results indicate the bison was most likely alive during Marine Isotope Stage 3. Sequential analyses of tooth enamel for strontium isotope ratios provide evidence for dispersal across the landscape. We indicate that ancient bison adopted different degrees of paleo-mobility according to the prevailing paleoenvironmental conditions.